Clinical Application of Different Vertical Position Tests for Posterior Canal-Benign Paroxysmal Positional Vertigo-Cupulolithiasis - Wang, Wenting; Yan, Shuangmei; Zhang, Sai; Han, Rui; Li, Dong; Liu, Yihan; Zhang, Ting; Liu, Shaona; Wu, Yuexia; Li, Ya; Yang, Xu; Gu, Ping (Frontiers in Neurology, 2022)
Background: Posterior canal-benign paroxysmal positional vertigo-cupulolithiasis (PC-BPPV-cu) is a new and controversial type of benign paroxysmal positional vertigo (BPPV). Whether the Half Dix-Hallpike test (Half D-HT) induces more obvious nystagmus than Dix Hallpike test(D-HT) and straight head hanging test (Shh) in patients with PC-BPPV-Cu. At present, there are few relevant clinical studies Objectives: To investigate the clinical characteristics of PC-BPPV-cu, and analyze the diagnostic significance of Dix-Hallpike test (D-HT), Half D-HT and straight head hanging (SHH) test in these patients. Methods: A total of 46 patients with PC-BPPV-cu were enrolled, and divided into two groups (N=23): a group A (induction order: D-HT, Half D-HT, SHH) and a group B (induction order: Half D-HT, D-HT, SHH). Results: Among 46 patients with PC-BPPV-cu, the bilateral and unilateral abnormality rates of the disease side were 5 cases and 41 cases, respectively. -There were significant differences in the proportion of torsional-upbeating nystagmus and upbeating nystagmus among the three headhanging positions in 46 patients with PC-BPPV-cu (P＜0.001). The slow phase velocity (SPV)of induced nystagmus at half D-HT supine position was slower than D-HT supine position(P<0.05) and SHH supine position (P<0.05). The nystagmus latency of D-HT supine position was significantly shorter than half D-HT (P<0.05) and SHH (P<0.05). PC-BPPV-cu patients were accompanied by 44.2% semicircular canal paresis, 54.4% audiological abnormalities, 76% cervical vestibular evoked myogenic potential (cVEMP) and 75% video head impulse test (vHIT) abnormalities, the concordance rates of the four detection methods were similar (χ2=0.243, P=0.970). Conclusions: The Half D-HT is simple and feasible, but might have a risk of false negative to diagnosis the torsional-upbeating nystagmus and upbeating nystagmus. The D-HT is still a classic induction method for PC-BPPV-cu. The two complement each other and may aid in the diagnosis of PC-BPPV-cu patients. Future clinical applications of Half D-HT require extensive research to determine its diagnostic efficacy.